2018
DOI: 10.3126/jmcjms.v5i2.19015
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the level of knowledge regarding the intramuscular administration of medication among staff nurses

Abstract: Background and Objectives: Intramuscular injection is an everyday procedure which is not without its hazards. Although insuring bodies have pointed out that the lateral thigh is the least unsafe site for an IM injection. The commonly used sites in the adult are gluteal and deltoid muscle. The present study was undertaken to assess the level of knowledge related to intramuscular administration of medication among staff nurses.Material and Methods: 30 samples were selected and descriptive research approach was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…Moreover, our result not compatible with Di Simone, et al, (2018) [6] who reported that, only 15.6% of nurses judged excellent their level of knowledge about preparation and administration of medications. However, our results contradict Kumar & Bashetti, (2017) [12] , who founded 46.67% had inadequate knowledge, 40% had moderate knowledge regarding the administration of medication. Moreover, Alan, (2019) [3] who founded that, 47.6% of the participants have good knowledge level regarding drug interactions and side effects of the drugs.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Moreover, our result not compatible with Di Simone, et al, (2018) [6] who reported that, only 15.6% of nurses judged excellent their level of knowledge about preparation and administration of medications. However, our results contradict Kumar & Bashetti, (2017) [12] , who founded 46.67% had inadequate knowledge, 40% had moderate knowledge regarding the administration of medication. Moreover, Alan, (2019) [3] who founded that, 47.6% of the participants have good knowledge level regarding drug interactions and side effects of the drugs.…”
Section: Discussioncontrasting
confidence: 92%
“…This finding agrees with a study was conducted by Abd Elmageed et al, (2020) [2] who found that slightly more than two fifths (40.7%) of the nurses were have diploma in nursing. Moreover, Kumar & Bashetti, (2017) [12] showed that the majority of staff nurses were educational status (60%) are having a diploma. The present study accepted with the study was conducted by Shamsuddin & Shafie, (2012) [15] , who found that, the majority of the respondents were diploma holders.…”
Section: Discussionmentioning
confidence: 99%
“…found 55.9% had correct information that two-handed recapping is not a safe injection practice. 7 Findings of the current study shows, regarding colour bin for immediate segregation of syringe, most of respondents 62 (79.5%) had correctly answered as red colour bin. But a study done in Kashmir, India showed that out of 152 injection providers, only 30.9% had correct knowledge regarding segregation of waste in colour coded bins.…”
Section: Methodsmentioning
confidence: 58%
“…12 Another study among 30 staff nurses in Kerala, India, showed significant association between age and educational status with level of knowledge regarding IM injection. 7 An analytical study from Panjab, India, revealed no significant association of IM injection with age, educational qualification and work experience. 8 Some of the limitations of this study include the observation of practice regarding safe IM injection was done after obtaining informed consent which may affect the results towards best practices due to Hawthorne effect.…”
Section: Methodsmentioning
confidence: 98%